Pupil response to accommodation and convergence in healthy children and adolescents of various age groups and autonomic nervous system tone - Shakir Dukhayer; N.M. Bushuieva; S.B. Slobodianyk (Ukrainian Society of Ophthalmologists, 2020)
Background: As there is close association between pupil response and accommodation during gaze fixation on an object at any distance, it is important to assess accommodative pupil response both in healthy children and in those with accommodative disorders. It is also important to assess relationships of characteristics of pupil response to accommodation and convergence with age and autonomic nervous system (ANS) tone. It is hypothesized that pupillography parameters can be regarded as objective criteria for assessing pupil response to accommodation and convergence, and serve as an important consideration in choosing the treatment method in patients with accommodative disorders. Purpose: To assess pupil response to accommodation and convergence in healthy children and adolescents of various age groups and autonomic nervous system (ANS) tones. Material and Methods: Pupil response to accommodation and convergence was studied in 269 systemically and ophthalmologically healthy children and adolescents (538 eyes) aged 6 to 18 years. Subjects were divided into three groups based on their age: group 1 (6-9 years; 77 subjects), group 2 (10-14 years; 96 subjects), and group 3 (15-18 years; 96 subjects). ANS tone was assessed using the Kerdo index. Pupillography studies were performed using an OK-2 pupillographer (Odesa, Ukraine). Pupil area, amplitude of change in pupil area, and duration of phases of change in pupil area were determined. Results: We determined normative values for pupillographic characteristics for 6-9, 10-14 and 15-18 years age groups with various ANS tones (increased parasympathetic, normal or increased sympathetic tone). In addition, we determined whether these characteristics depend on the child's age and/or balance of autonomic innervation. There was pupillographic evidence that those with increased sympathetic tone had significantly greater pupil area and amplitude of changes in pupil area, and significantly shorter timing of changes in pupil size than those with normal ANS tone or increased parasympathetic tone. The fact that younger children (i.e., those aged 6-9 years) had slower pupil response to accommodation and lower amplitude of change in pupil area compared to older children and adolescents (i.e., those aged 10-18 years) may indicate a low level of structural and functional maturity of the accommodative and convergence system at this age. Conclusion: The patterns of relationships revealed in the study provide grounds for regarding pupillography data as an objective criterion for assessing the pupil response to accommodation and convergence and the balance of ANS innervation in children and adolescents of various age groups.